Evaluation of light guide plate (lgp) micropattern form accuracy fabricated via direct co2 laser structuring - Norfazilasari, Yasman (2025)
CO2 direct laser structuring has emerged as a promising and cost-effective method to fabricate various micropatterns on different substrate materials. This includes direct laser patterning on transparent substrate for light guide plate (LGP) applications. However, obtaining desired pattern design quality and performance consistently on the substrate surface poses challenges. In this research, CO2 laser structuring of two types of micropatterns; micro-dots and straight parallel microchannel on PMMA polymer and KPSFn214 optical glass substrates was demonstrated. The study explores the feasibility of employing these micropatterns for LGP applications and assesses their potential for enhancing luminance output. Laser scanning parameters, specifically laser power, laser scanning speed and number of laser passes on the formation of micropatterns width (µm), diameter (µm) and height (µm) were investigated. The form accuracy, including the heataffected zone (HAZ) and surface roughness (µm) of the micropatterns was then characterized using laser scanning confocal microscope (LSCM) and surface profiler. The results indicate successful formation of micro-dots patterns with diameters ranging from 170 µm to 114 µm through focused laser structuring. These patterns emerged as a result of varying laser power of 2 W to 10 W and laser scanning speed of 1000 mm/sec to 3000 mm/sec during a single pass of the laser without preheating. The study revealed that both the diameter and height of the micro-dots pattern increased with higher laser power, whereas increasing laser scanning speeds resulted in reduced diameter and height of the micro-dots. Additionally, the shape of the micro-dots varied from circular to elliptical. As the laser power increased, particularly at 6 W, the removal zone exhibited a more elliptical shape compared to the shape observed at 2 W, indicates the influence of laser power on the geometry of the removal zone. In addition, this experiment also examined the effect of different number of laser passes, ranging from a single to ten passes. In the case of micro-dots patterns on PMMA, the diameter varied approximately from 200 µm to 450 µm, with height ranging from 30 µm to 480 µm. Meanwhile, for straight parallel microchannels, the width ranging from 320 µm to 370 µm, with heights varied from 50 µm to 250 µm. Through observation, it was noted that as the number of laser passes increased, the diameter, width and height also increased until reaching a point where the height remained constant. This was occurred because the laser beam was no longer hits its focal point. An increase in the number of laser passes also contributed to a more pronounced and well-defined micropattern, particularly in terms of enhanced surface roughness and reduced HAZ. Moreover, on the non-preheated glass substrate, the formation of discontinuous peeling of the glass strip was noticed at a laser scanning speed of 800 mm/sec and laser power of 30 W. The layer of glass become softened, leading to deformation or bending. Finally, as a practical application, the study demonstrated the optical performance of the fabricated PMMA LGP and investigated the impact of both micropatterns on its performances. It was observed that straight parallel microchannels exhibit higher luminance higher at 1757.67 cd/m2 compared to micro-dots at 1730.26 cd/m2 . The lower luminance reading of the micro-dots was due to their smaller surface area and the potential for more light scattering due to their shape and arrangement.